Characteristics of the board of directors and dividend policy: A case study of banks in Western Balkans - Marko Milašinović; Aleksandra Radojević; Biljana Jovković (Naše gospodarstvo / Our Economy, 2023)
This paper examines the influence of the size and participation of women in the board of directors on the dividend policy of banks in Western Balkans. The research covered 104 banks, observing their dividend policy from 2017 to 2019. The dividend payout ratio was measured by the dividend policy. A relatively small number of banks paid dividends during the observation period. By applying the Fixed-Effect model, it was determined that the size of the board of directors has a statistically significant positive impact on the dividend policy of observed banks. Concerning the participation of women on the board of directors, a statistically significant impact on the dividend policy of banks was not identified. In addition to contributing to the existing literature on corporate finances, the research results can be crucial to investors when deciding to invest funds in bank stocks.
Keywords: G21; G30; 330; Banks; Board of directors; Gender structure; Dividend policy; Western Balkans